Women And Islam Disability in Literary Work of Ratna Indraswari Ibrahim - Mansurudin, Susilo (Cultural Narratives, 2024)
This study investigates the intersection of women, Islam, and disability as represented in the literary works of Ratna Indraswari Ibrahim (RII), a disabled woman author. RII's work is significant for its advocacy of women's independence and equality with men, while also highlighting the potential and agency of people with disabilities. The research aims to uncover how RII, as a disabled author, promotes innovation, independence, and resilience in the face of life's challenges. Employing a qualitative methodology, this study analyzes RII's writings through the lens of hermeneutic theory, encompassing textual, contextual, and critical interpretations. Feminist theory is also utilized to examine RII's personal advocacy for women's dignity. Data, derived from RII's authorship and literary works. This research lies in its unique intersectional approach, examining the representation of women, Islam, and disability in the work of a single author. The study reveals that while the struggles and rights of women, as portrayed in RII's novels, align with Islamic values of equality as found in the Qur'an, the lived experiences of people with disabilities often fall short of this ideal. RII's work seeks to challenge societal perceptions and advocate for justice and inclusivity, aiming to transform perspectives on disability and promote equality in all aspects of life. This study has the potential to contribute to a deeper understanding of the representation of disability in literature, particularly within the context of Islamic and feminist discourses. It can inform discussions on social justice, inclusivity, and the rights of marginalized groups.